Growth of C‐S‐H phases on different metallic surfaces. (25th February 2022) - Schleiting, Maximilian; Wetzel, Alexander; Göbel, Daniela; Krooß, Philipp; Frenck, Johanna‐Maria; Niendorf, Thomas; Middendorf, Bernhard
Abstract: The influence of reinforcement, especially fibre reinforcement in ultra‐high performance concrete is strongly dependent on the bonding (adhesive, shear and friction bond) between metallic surface and cementitious matrix. As usually straight fibres are used for fibre reinforcement and, thus, no significant mechanical bonding is existent, the adhesive bond is particularly important. Previous studies stated that the adhesive bonding behaviour between metallic materials and cementitious matrix strongly depends on the chemical composition of metallic alloys. Therefore, in order to address this topic, the present study investigates the growth of C‐S‐H phases on stainless steel and on cold drawn steel. This growth process was realised by a surface treatment of the metallic alloys using a synthetically manufactured Tricalciumsilicate (C3 S) powder diluted in water. After defined times of the C3 S treatment the process is stopped to get a time dependent growing behaviour of the cementitious phases. Light microscopy as well as scanning electron microscopy was used in order to investigate the surfaces following the application of the C3 S. The results reveal that the growth of C‐S‐H phases is more dependent on the metallic surface and its topography than on the alloy composition.